2022
DOI: 10.1016/j.celrep.2022.110344
|View full text |Cite
|
Sign up to set email alerts
|

Mutations that adapt SARS-CoV-2 to mink or ferret do not increase fitness in the human airway

Abstract: SARS-CoV-2 has a broad mammalian species tropism infecting humans, cats, dogs and farmed mink. Since the start of the 2019 pandemic several reverse zoonotic outbreaks of SARS-CoV-2 have occurred in mink, one of which reinfected humans and caused a cluster of infections in Denmark. Here we investigate the molecular basis of mink and ferret adaptation and demonstrate the spike mutations Y453F, F486L, and N501T all specifically adapt SARS-CoV-2 to use mustelid ACE2. Furthermore, we risk assess these mutations and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 57 publications
(62 reference statements)
2
59
0
Order By: Relevance
“…Meanwhile, our functional prediction analyses using bioinformatic approaches suggest a minimal impact of all strong candidate Spike mutations, including Spike_F486L, on Spike: mink-ACE2 interactions. This is despite in vitro evidence that these three mutations allow more efficient cellular entry into cells expressing mustelid ACE2 54 . Further, while the strong candidate spike mutations Y453F and N501T were found to improve Spike:human-ACE2 interactions 56 , we find that they confer minimal or no evolutionary advantage for transmission in humans, concordant with in vitro evidence that Y453F attenuates SARS-CoV-2 in human bronchial cells 54 .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Meanwhile, our functional prediction analyses using bioinformatic approaches suggest a minimal impact of all strong candidate Spike mutations, including Spike_F486L, on Spike: mink-ACE2 interactions. This is despite in vitro evidence that these three mutations allow more efficient cellular entry into cells expressing mustelid ACE2 54 . Further, while the strong candidate spike mutations Y453F and N501T were found to improve Spike:human-ACE2 interactions 56 , we find that they confer minimal or no evolutionary advantage for transmission in humans, concordant with in vitro evidence that Y453F attenuates SARS-CoV-2 in human bronchial cells 54 .…”
Section: Discussionmentioning
confidence: 92%
“…Our analyses, focusing on a set of criteria applied to recurrent mutations, identify putative signatures of host adaptation following onward transmission of SARS-CoV-2 in mink and deer. The spike mutations N501T, F486L and Y453F have been shown to improve entry into cells expressing ferret ACE2 and are therefore animal adaptive 54 . Further, phylodynamic analyses of Dutch mink farm outbreaks have previously shown that viruses in minks that carry the Spike_F486L mutation may evolve and transmit at a faster rate 55 .…”
Section: Discussionmentioning
confidence: 99%
“…Two mutations in the S protein, F486L and N501T have been associated with mustelid (mink or ferret) host adaptations, and N501T has been associated with enhanced ACE2 binding and entry into human (Huh7) cells (Han et al, 2021; Lu et al, 2021; Oude Munnink et al, 2021; Starr et al, 2020). Notably, the Ontario WTD SARS-CoV-2 genomes did not harbour the relatively well-described S:Y453F mutation associated with mink and increased replication and morbidity in ferrets, but reduced replication in primary human airway epithelial cells (Zhou et al, 2022). These WTD genomes provide new insights into viral evolution and inferred virus mobility in animal species outside of the human population.…”
Section: Discussionmentioning
confidence: 99%
“…Reverse genetics derived viruses were generated as previously described 12,52,53 . Briefly, recombinant SARS-CoV-2 Wuhan cDNA genomes bearing the D614G, or Delta spike- or Omicron spike-encoding sequence were generated from a set of relevant overlapping genomic cDNA fragments and assembled using the Transformation-Associated Recombination (TAR) in yeast method as described 12 .…”
Section: Methodsmentioning
confidence: 99%